Return Migration in the Face of Environmental Changes - Dufková, Šárka (2019)
This paper aims to investigate variables describing the phenomenon of return migration and its possible significance. Moreover, it aims to look at the connection between return migration and environmental changes. The analysis makes use of rich data derived from Gallup Word Poll database describing a variety of relevant variables. Linear Probability Model is used to run regressions with given variables. The main focus is firstly on the global control variables and their effect on return migration and secondly on the variables describing environmental changes and their effect on the given phenomenon. However, other variables such as time-varying country characteristics are introduced. Furthermore, specific regressions focused on the importance of the level of income of individuals and on the country’s´ membership in OECD are described.